Hybrid Voting Model for Tackling Voter’s Apathy in 2023 Governorship Election In Kaduna State - Abubakar , Mohammed Munir; Ibrahim, Bashir (Kashere Journal of Politics and International Relations, 2025)
It is obvious that in 2023 election in Nigeria, only 24.9% of the electorate voted in the presidential poll. To make voting comfortable largely to improve the voters’ turnout, this study proposed a robust model with a hybrid approach that comprise the conventional voting and electronic voting that could allow voters to use their cellphones, tabs and computers to cast their votes. The study underpinned by two theories: Democratic theory which assumed that electoral technologies have an impact on improving values such as transparency and citizen participation in governance and Technology Acceptance Theory that postulated by Ajzen and Fischbein which assumed that the positive intention of the technology users to adopt technology could largely improve their productive performance and the attitude of the users to accept the positive product of technology for the reduction of human errors. A multistage sampling technique was used for this study to select six local governments two each from three senatorial districts in Kaduna Sate. Interview were conducted with the cyber security experts and INEC officials in order to assess INEC cyber capacity in receiving, transmitting and storing the data receive from the voters via internet devices. The study found that Hybrid Voting Model could be instrumental in making voting more easily, voters’ friendly and consequently tackling the growing challenge of voters’ apathy in Nigeria. The study recommends that Nigerian government need to allocate sufficient fund to its ICT department to extent and improve the internet network and penetration to every section of Nigeria.